Components and determinants of therapeutic delay in patients with acute ST-elevation myocardial infarction A tertiary care hospital-based study - Beig, Jahangir Rashid (Journal of the Saudi Heart Association, 2017)
BACKGROUND: Delayed reperfusion is associated with worse outcomes in ST-segment elevation myocardial infarction (STEMI). This study was conducted to assess the components and determinants of therapeutic delay in STEMI patients of our state